2019
DOI: 10.1186/s13756-019-0638-8
|View full text |Cite
|
Sign up to set email alerts
|

APSIC guidelines for the prevention of surgical site infections

Abstract: BackgroundThe Asia Pacific Society of Infection Control (APSIC) launched the APSIC Guidelines for the Prevention of Surgical Site Infections in 2018. This document describes the guidelines and recommendations for the setting prevention of surgical site infections (SSIs). It aims to highlight practical recommendations in a concise format designed to assist healthcare facilities at Asia Pacific region in achieving high standards in preoperative, perioperative and postoperative practices.MethodThe guidelines were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 49 publications
3
67
2
16
Order By: Relevance
“…It has been shown that older people are more likely to develop SSI [16] ; in this study, age was not a predictor as observed using multivariate logistic regression analysis. Male patients had a signi cantly higher risk of SSI after EAS than females (OR 2.204, 95% CI 1.178 -8.985, P = 0.010); while this is partly debated, multiple studies have found signi cantly higher rates of SSI in male patients than in females [17,18].…”
Section: Discussioncontrasting
confidence: 53%
“…It has been shown that older people are more likely to develop SSI [16] ; in this study, age was not a predictor as observed using multivariate logistic regression analysis. Male patients had a signi cantly higher risk of SSI after EAS than females (OR 2.204, 95% CI 1.178 -8.985, P = 0.010); while this is partly debated, multiple studies have found signi cantly higher rates of SSI in male patients than in females [17,18].…”
Section: Discussioncontrasting
confidence: 53%
“…From this review, we found that the guidelines from Bangladesh, 32,116,127 Indonesia, 36,118,119 and South Korea 35,121,122 were not culturally grounded in regard to IPC guidelines and policy in acute care facilities. In fact, the contents in the guidelines were very similar to those in the WHO, CDC, Canada, Australia, and United Kingdom, except that they lacked the references to the use of patient empowerment and engagement in hand hygiene.…”
Section: Discussionmentioning
confidence: 94%
“…Considering the in-depth involvement of family carers in the care, the definition of carer from the western countries could not embrace the role of carers in the target countries. Despite the care activities family members and privately hired carers perform, their roles or responsibility could not be located in any guidelines from Bangladesh, 32,116,127 Indonesia, 36,118,119 and South Korea. 35,121,122 IPC strategies for family carers not considered…”
Section: Definition Of Carermentioning
confidence: 99%
See 1 more Smart Citation
“…SSI is the most common hospital-acquired infection (HAI) in low-income and middle-income countries (LMICs) and the second or third most frequent HAI in high-income countries (HICs) [ 5 , 6 ]. In LMICs, the occurrence of SSI ranges from 6.1–7.8%, and for HICs, this occurrence ranges from approximately 1–3% [ 7 ]. Orthopaedic surgeries, such as hip and knee prosthesis, are among the highest cumulative incidences of SSI [ 5 ].…”
Section: Introductionmentioning
confidence: 99%